Effects of functional training on tennis-specific physical fitness and functional movement screen in junior tennis players - Xiao, Wensheng; Bai, Xiaorong; Soh, Kim Geok; Zhang, Yang (Public Library of Science, 2024)
Objectives Functional training mimics the coordinated motions of multiple muscle groups and joints performed during exercise. The purpose of this study was to compare the effects of a 12-week functional training and traditional resistance training on the performance in junior tennis players. Methods Trained tennis players (mean age: 16.6 years) were assigned to a traditional training group (n = 20) or functional training group (n = 20). The traditional training group received a resistance training program by their coach, while the functional training group was given Santana's Racket Sport Program. At baseline, after six weeks, and after 12 weeks (T12), the participants' tennis-specific physical fitness and functional movement screen (FMS) were evaluated. Results At T12, both training improved the values for multistage fitness test, hexagon test, planned agility test, sit and reach, and 20 metre sprint (p < 0.05); except the flexibility, functional training provided no additional advantages. At T12, functional training enhanced (p < 0.01) all seven components of the FMS, and there is a 100% probability that the total score of the FMS would be enhanced. In contrast, for the traditional training group, shoulder mobility of the FMS decreased (p = 0.03), and there was no changes in other FMS components at T12. Conclusions Functional training is not only effective in improving tennis-specific physical fitness, but it also provides greater functional movement advantages for junior tennis players compared to traditional resistance training.